Pemberdayaan Ibu Rumah Tangga Melalui Pembuatan Handsanitizer Dalam Upaya Pencegahan Covid-19 - Resti Utami; Gardina Aulin Nuha (Journal of Community Development, 2021)
Housewives have an important role to play in supporting government programs in preventing the spread of COVID-19 at the household level. Community service activities aim to provide understanding to partners so that they have knowledge and concern about preventing the spread of COVID-19 through the application of the 5M health protocol, increasing creativity in efforts to prevent the spread of COVID-19 through education on how to make hand sanitizers from natural ingredients of betel leaf (Piper betle Linn) which are mostly found in Sukorejo Village. The method used in this activity is counseling by providing material through lectures and distributing hand sanitizer finished products. The implementation of this service activity in the form of dissemination of the prevention of the spread of COVID-19 involves active participation from partners starting from the activity planning process, preparation of activity schedules to education on how to make and distribute hand sanitizers. This activity generated ideas for partners who are mostly housewives to empower themselves in supporting government programs to prevent the spread of COVID-19 by practicing how to make natural hand sanitizers from betel leaf. Thus, the expected output from this activity is an increase in IRT knowledge in preventing the spread of COVID-19, how to manufacture, packaging hand sanitizers, and participants to obtain sample products which can increase interest in producing similar products and commitment to implementing health protocols in preventing the spread of COVID-19.